Human and Divine in the Poetry of Walt Whitman - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education; Vol 6 No 4 (2021): Journal of Advanced Research in English and Education, 2021)
Materialism and spiritualism are major themes of Whitman’s poetry. A man can be worldly-wise and yet spiritual. For Whitman, materialism and spiritualism can co-exist perfectly. So, according to Whitman, if people are desirous of getting worldly pleasure, it does not make them less connected with God. We cannot be less spiritualistic than those who worship God and offer prayers to Him. Spiritualism is that constant search, more inner than outer, that enables us to know what we are. Whitman looks upon each and everyone as spiritual. For him, it is the body that shows the way to the soul and the soul shows the way to God. We see a gradual shift of emphasis from the material to spiritual in the poetry of Walt Whitman. How to cite this article: Priydarshi AK. Human and Divine in the Poetry of Walt Whitman. J Adv Res Eng & Edu 2021; 6(4): 1-4. DOI: https://doi.org/10.24321/2456.4370.202106